Experimental Investigation into the Mechanical Performance of Roadway Shotcrete with the Partial Replacement of Cement with Recycled Gangue Powder - Shoubiao Li; Xiaolong Wang; Ruimin He; Yong Zhang; Shilong Kang (Applied Sciences)
To maximize the comprehensive utilization of gangue waste, broken gangue can be used to replace gravel as the coarse aggregate to prepare underground roadway shotcrete, and treated gangue powder can be used for the partial replacement of cement. This not only diminishes the demand for conventional raw materials but also increases the amount of gangue waste disposed. Broken gangue waste was ball-milled for 1 h, 3 h, and 5 h to prepare gangue powder, which was used to partially replace cement. Then, experimental schemes for the performance of shotcrete at the rates of cement replacement of 30%, 40%, and 50% were devised to compare the mineral compositions and microscopic characteristics of shotcrete with the partial replacement of cement with gangue powder. The influences of the partial replacement of cement with gangue powder on the slump, tensile strength, and compressive strength of the shotcrete were revealed. The experimental results revealed an inverse relationship between shotcrete slump and both the cement replacement ratio and the gangue Ball-milling duration. Increasing the cement replacement ratio from 30% to 50% reduced slump by 55.3% (103 mm → 46 mm), while extending the Ball-milling time from 1 h to 5 h decreased it by 33.0% (103 mm → 69 mm). Mechanical properties showed contrasting trends: After a 28-day curing process, compressive and tensile strengths declined by 54.5% (20.18 → 9.18 MPa) and 40.4% (1.56 → 0.93 MPa), respectively, with a higher cement replacement ratio. Conversely, prolonged Ball-milling duration improved the compressive strength by 12.8% (18.68 → 21.07 MPa) and the tensile strength by 34.1% (1.26 → 1.69 MPa). Moreover, the shotcrete meets the strength requirements for engineering applications only when the cement replacement ratio is 30% with gangue ball-milling durations of 3 h and 5 h. The research provides strong support for the performance optimization of gangue-based shotcrete and the improvement of the utilization of gangue waste.